Окружение Сталина - Медведев Рой Александрович (Жизнь замечательных людей, 2010)
Экземпляры: 1 (20121126) / Инвентарный номер: 56241 / Цена: 288.53 / Сис.шифр: 63.3(2) / Авт.знак: М 42 / ГРНТИ: 03.23 / ББК: 63.3(2)